Experience in the design of external protection systems against lightning - Arnera, Patricia Liliana (1999)
This paper describes the experience acquired during the revision and determination of external lightning protection systems in some refinery plants, in Argentina. With this purpose a program, developed by IITREE, based on the Monte Carlo statistical technique, was used, among other things, to determine in a period of time the frequency of lightning flashes to structures. International and American standards were used as reference.